A genre analysis of the results and discussion section of masters dissertations / Naima Manzur - Naima , Manzur (2019)
Academic institutions and different academic communities around the world have been concerned about students’ academic writing. As academic writing is highly challenging particularly for non -native English language users; accordingly, in recent years an increase in academic genre analysis is noticeable. Unlike other genres, the Master’s dissertations have remained much understudied. As in reporting research findings novice writers’ face many difficulties thus an investigation on the result and discussion sections is essential. Previous genre analysis in the academic genre field was focusing on abstract and introductions chapters of masters’ dissertations. A very few studies looked at the result and discussion chapters written particularly by ESL writers’. Together with, in producing an effective result report writing also needs to be persuasive. A well-organized text is effective in convincing the target readers. This genre based text analysis study presents an analysis of ten (10) Applied Linguistics (AL) Master’s dissertations combined result and discussions (R&D) chapters. The aim of the present study is to identify the communicative purpose and the general pattern of the genre. This study also aims to look at the interactional metadiscourse of the R&D chapter. It is based on the move-step tradition initiated by Swales (1990) to develop his influential Create a Research Space (CARS) model for research article introductions and on Nguyen and Pramoolsook (2015) framework. This mixed method study found that the main communicative purpose of the combined R&D is not only to introduce the chapter and report the results or findings but to comment and summaries the results as well. The move frequency is classified by following Kanoksilapatham’s (2005) work. A cyclical pattern of (M2) reporting result-(M3) commenting on the result- (M2) reporting result appeared frequently in the ESL writing. Analysis of hedges, boosters, and engagement markers further present the interactional practice of the ESL community. The communicative purposes of the ESL dissertations are organized mostly with booster markers. The finding indicates writers’ awareness about the target audience.